2020
DOI: 10.1038/s41598-020-60027-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic reference values for sarcopenia in Tibetans in China

Abstract: Sarcopenia is an age-associated disease characterized by loss of muscle mass and function, but the diagnostic cutoff values remain controversial. To investigate the diagnostic cutoff values and incidence of sarcopenia in a plateau population, the limb skeletal muscle mass, gait speed and grip strength of 2318 Tibetan adults were measured according to the criteria of the Asian Working Group for Sarcopenia. We found that the diagnostic reference values for sarcopenia in the high-altitude population were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 28 publications
(16 reference statements)
2
20
0
Order By: Relevance
“…Therefore, it may play a role in the development of sarcopenia in humans. In previous research, the incidences of sarcopenia in Tibetans over 60 were 17.2% in men and 36.0% in women, significantly higher than those in the plain population (Ye et al, 2020). Tibetans are an archaic ethnicity (Lu et al, 2016), have lived at very high altitudes for thousands of years, and have a distinctive suite of genetic traits that enable them to tolerate environmental hypoxia (Simonson et al, 2010; Song et al, 2020), which make them significantly different from the Han and other plain populations genetically (Beall et al, 2010).…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, it may play a role in the development of sarcopenia in humans. In previous research, the incidences of sarcopenia in Tibetans over 60 were 17.2% in men and 36.0% in women, significantly higher than those in the plain population (Ye et al, 2020). Tibetans are an archaic ethnicity (Lu et al, 2016), have lived at very high altitudes for thousands of years, and have a distinctive suite of genetic traits that enable them to tolerate environmental hypoxia (Simonson et al, 2010; Song et al, 2020), which make them significantly different from the Han and other plain populations genetically (Beall et al, 2010).…”
Section: Introductionmentioning
confidence: 84%
“…According to the recommended diagnostic AWGS algorithm, GS, HS, and skeletal muscle mass index (SMI) were the primary indicators for sarcopenia diagnosis (Chen et al, 2014). The cutoff values for SMI measurements were 8.07 kg/m 2 for men and 6.62 kg/m 2 for women (Ye et al, 2020). Low physical performance was defined as a GS less than 0.8 m/s (Ye et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight loss has been widely reported in hypoxic chamber experiments and after sojourns at high altitudes (5)(6)(7). Some studies have found that skeletal muscle mass decreased with increasing altitude as the hypoxic environment accelerated the decomposition of skeletal muscle and inhibited protein synthesis (8,9). Muscle weakness is a key factor in the increased risk of falls and might also play a significant role in the increased risk of hip fracture (10,11).…”
Section: Introductionmentioning
confidence: 99%